2019
DOI: 10.1038/s41390-019-0518-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive analytics in the pediatric intensive care unit for early identification of sepsis: capturing the context of age

Abstract: BACKGROUND: Early recognition of patients at risk for sepsis is paramount to improve clinical outcomes. We hypothesized that subtle signatures of illness are present in physiological and biochemical time series of pediatric-intensive care unit (PICU) patients in the early stages of sepsis. METHODS: We developed multivariate models in a retrospective observational cohort to predict the clinical diagnosis of sepsis in children. We focused on age as a predictor and asked whether random forest models, with their p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…10,11,13,15 To accept new tools like predictive analytics, particularly those that derive information from the physiologic waveforms, clinicians need to understand what is happening inside. 11,13,16,17 We presented the published evidence base 6,[18][19][20][21][22] to provide transparency into the algorithms' underpinnings and to emphasize the strengths of the scientific foundation. 16 We focused other sessions on current patients to give clinicians a more detailed examination of how data elements interacted within the algorithm to produce a risk score.…”
Section: Frameworkmentioning
confidence: 99%
“…10,11,13,15 To accept new tools like predictive analytics, particularly those that derive information from the physiologic waveforms, clinicians need to understand what is happening inside. 11,13,16,17 We presented the published evidence base 6,[18][19][20][21][22] to provide transparency into the algorithms' underpinnings and to emphasize the strengths of the scientific foundation. 16 We focused other sessions on current patients to give clinicians a more detailed examination of how data elements interacted within the algorithm to produce a risk score.…”
Section: Frameworkmentioning
confidence: 99%
“…Continuous electrocardiogram data from bedside monitors, vital signs, laboratory values, and clinical assessment findings in the electronic health record can be analyzed to identify patients at rising risk of sepsis, prior to overt clinical signs. Predictive models exist that were developed as time series measures of changing risk based on clinical variables that detect physiological changes with illness (5)(6)(7)(8)(9). The utility of such continuous predictive analytics is intuitive: novel monitoring to alert busy clinicians to a change in the patient so diagnosis and treatment can occur early.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous monitoring in children can be challenging to implement because it can be difficult to keep continuous monitoring leads and probes on mobile children, and previous estimates have demonstrated as few as 1% of alarms in children are clinically meaningful [29]. We speculate that there can be clinical benefit to shifting the clinical monitoring paradigm away from its use only as a means of responding to critical physiological alarms and towards a means for early detection of clinical deterioration using continuous predictive analytics monitoring so clinicians can initiate proactive clinical actions [28,30,31]. To avoid medical overuse and further contribution to false alarms, there is a defined need to determine the populations that could benefit the most from continuous cardiorespiratory monitoring in the acute care pediatric setting while also determining the correct "dose" of continuous cardiorespiratory monitoring for those at risk of clinical deterioration.…”
Section: Discussionmentioning
confidence: 94%
“…Further, there is substantial heterogeneity in ages represented in any pediatric sample. When Spaeder and colleagues [28] developed a machine learning model to predict early onset of pediatric sepsis, they found that parameters performed differently in the model given the age of the pediatric patient, again indicating that no one model likely performs equally well in all age ranges represented in pediatric care (neonate, infant, child, adolescent).…”
Section: Discussionmentioning
confidence: 99%